An electrochemical sensor based on graphene oxide/cholesterol nanohybrids for the sensitive analysis of cetirizine. Issue 6 (December 2022) - Killedar, Laxmi S.; Shanbhag, Mahesh M.; Manasa, G.; Malode, Shweta J.; Veerapur, Ravindra S.; Shetti, Nagaraj P.; Mascarenhas, Ronald J.; Kakarla, Raghava Reddy
Abstract: Cetirizine (CTR) is second-generation piperazine that belongs to the class of antihistamine that helps reduce allergies. The present research reports on the fabrication of CTR-sensitive sensors for electrochemical detection and quantification of CTR. The electrochemical behavior of CTR was studied utilizing a carbon paste-based electrode (CPE) modified with 2D graphene oxide (GO) and cholesterol (CHO). The facile construction of this sensor was achieved by loading the homogenized CHO-GO/CP (cholesterol-graphene oxide nanohybrid-modified carbon paste) matrix into a polytetrafluoroethylene (PTFE) tube. The surface morphology of the developed sensor's matrix was carried out employing SEM and AFM. The obtained results convey that fabricated CHO-GO/CPE is relatively more CTR sensitive than CPE or step-wise modified electrodes such as CHO/CPE and GO/CPE. The detection limit of CTR at CHO-GO/CPE was determined to be 9.2 nM. Further, the electrochemical impedance spectroscopy investigation (EIS) showed that CHO-GO/CPE offered less resistance to charge transfer than CPE. Additionally, participation of the total number of charges in the CTR electro-oxidation mechanism, the standard reduction potential of CHO-GO/CPE, charge transfer coefficient, and heterogeneous rate constants were estimated using the effect of the electrolyte's pH and scan rate variation investigation results. Moreover, adding several excipients to the CTR analyte did not affect the overall electrochemical behavior of CTR, thus confirming the anti-interference characteristics of the fabricated sensor. To evaluate the sensor's efficiency for a real-time application, CTR detection in tablet solutions was investigated, and the results demonstrated remarkable detection with good recovery. Graphical Abstract: ga1 Highlights: CHO-GO/CPE was successfully used in the sensing of pharmaceuticals (CTR). Two-fold enhanced peak current obtained at the revised electrode. CTR determination was done successfully in presence of metal ion and excipients. Quantification limit was found to be of 9.2 nM for CHO-GO/CPE. Nano-sensors have potential applications in environmental sensing and monitoring.